Identification and analysis of damaged or porous hair. Issue 1 (June 2014) - Hill, Virginia; Loni, Elvan; Cairns, Thomas; Sommer, Jonathan; Schaffer, Michael; Agius, Ronald
<x xml:space="preserve">Abstract</x> Cosmetic hair treatments have been referred to as 'the pitfall' of hair analysis. However, most cosmetic treatments, when applied to the hair as instructed by the product vendors, do not interfere with analysis, provided such treatments can be identified by the laboratory and the samples analyzed and reported appropriately for the condition of the hair. This paper provides methods for identifying damaged or porous hair samples using digestion rates of hair in dithiothreitol with and without proteinase K, as well as a protein measurement method applied to dithiothreitol‐digested samples. Extremely damaged samples may be unsuitable for analysis. Aggressive and extended aqueous washing of hair samples is a proven method for removing or identifying externally derived drug contamination of hair. In addition to this wash procedure, we have developed an alternative wash procedure using 90% ethanol for washing damaged or porous hair. The procedure, like the aqueous wash procedure, requires analysis of the last of five washes to evaluate the effectiveness of the washing procedure. This evaluation, termed the Wash Criterion, is derived from studies of the kinetics of washing of hair samples that have been experimentally contaminated and of hair from drug users. To study decontamination methods, in vitro contaminated drug‐negative hair samples were washed by both the aqueous buffer method and a 90% ethanol method. Analysis of cocaine and methamphetamine was by liquid chromatography‐tandem mass spectrometry (LC/MS/MS). Porous hair samples from drug users, when washed in 90% ethanol, pass the wash criterion although they may fail the aqueous wash criterion. Those samples that fail both the ethanolic and aqueous wash criterion are not reported as positive for ingestion. Similar ratios of the metabolite amphetamine relative to methamphetamine in the last wash and the hair is an additional criterion for assessing contamination vs. ingestion of methamphetamine. Copyright © 2014 John Wiley & Sons, Ltd.